Supersensitive detection of single-histamine molecule on nanoplates by turn-on small molecule fluorescence sandwich immunoassay. Issue 4 (24th January 2023) - Lee, Seungah; Lee, Junghwa; Kang, Seong Ho
Abstract : Turn-on small molecule fluorescence sandwich immunoassay. Abstract : We develop a supersensitive "turn-on format" fluorescence sandwich immunoassay for detecting small single molecules. Gold nanoplate-based biotin antibodies and streptavidin–fluorophores were used instead of streptavidin–horseradish peroxidase reacting with a biotin tracer in a microplate-based competitive enzyme-linked immunosorbent assay (ELISA). Our platform showed a low detection limit of 5 zeptomolar (5 × 10 –21 M), 5.4 × 10 10 times higher detection sensitivity than the conventional tune-off format ELISA.